1993
DOI: 10.1063/1.530056
|View full text |Cite
|
Sign up to set email alerts
|

Finite Lorentz transformations, automorphisms, and division algebras

Abstract: We give an explicit algebraic description of finite Lorentz transformations of vectors in 10-dimensional Minkowski space by means of a parameterization in terms of the octonions. The possible utility of these results for superstring theory is mentioned. Along the way we describe automorphisms of the two highest dimensional normed division algebras, namely the quaternions and the octonions, in terms of conjugation maps. We use similar techniques to define SO(3) and SO(7) via conjugation, SO(4) via symmetric mul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
167
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(170 citation statements)
references
References 14 publications
3
167
0
Order By: Relevance
“…In this case a Hilbert space formulation is not possible due to the nonassociative nature of the octonions. It has, however, been shown that the usual axioms of quantum theory may be satisfied by taking a more abstract "propositional" approach [194,214,217,219,220]. Let us compare J 3 (P ) of section 9.4 with the 2 qutrit reduced matrices ρ A and ρ B ρ A = Tr B |Ψ Ψ|, ρ B = Tr A |Ψ Ψ|, (13.30) which are also 3 × 3 hermitian and transform in the same way, at least in the R and C cases:…”
Section: The Jordan Algebra Formulation Of Quantum Mechanicsmentioning
confidence: 99%
“…In this case a Hilbert space formulation is not possible due to the nonassociative nature of the octonions. It has, however, been shown that the usual axioms of quantum theory may be satisfied by taking a more abstract "propositional" approach [194,214,217,219,220]. Let us compare J 3 (P ) of section 9.4 with the 2 qutrit reduced matrices ρ A and ρ B ρ A = Tr B |Ψ Ψ|, ρ B = Tr A |Ψ Ψ|, (13.30) which are also 3 × 3 hermitian and transform in the same way, at least in the R and C cases:…”
Section: The Jordan Algebra Formulation Of Quantum Mechanicsmentioning
confidence: 99%
“…The following two lemmas are essentially contained in [38], but we would like to present a proof for the sake of completeness.…”
Section: Remarkmentioning
confidence: 99%
“…More details specifically about the effects of the non-associativity of the octonions are given in [13,14].…”
Section: B Lorentz Transformationsmentioning
confidence: 99%
“…Only general properties of octonions independent of a specific multiplication table will be used here. However, because we make frequent use of a variety of octonionic identities, the reader may find more information on octonions helpful; see [14,15].…”
Section: A Octonionic Spinorsmentioning
confidence: 99%